What Art and Design Do for Social Inclusion in the Public Sphere - Hannes, Karin (2021)
Art and design can meaningfully contribute to social change. It can shift debates, change perspectives, raise awareness, and act upon visible and invisible mechanisms of inclusion and exclusion of different agents occupying the public sphere. In this thematic issue we invited authors to relate to this claim as they preferred: by bringing evidence to support it, refute it, or simply to discuss the potential benefits and harms of artistically inspired and design related interventions in citizens living environment. We challenged authors to rethink agency and engage theoretically or empirically with how art and design installations act upon us, citizens, and vice‐versa. The result is a compilation of different storylines, coming from different geographical parts of the world and written from a variety of cultural perspectives. What binds these contributions is a true commitment to open up a space for those experiencing challenging life circumstances to access, occupy, or transform the public sphere. Our collective engagement with concepts such as power, prejudice, harassment or discrimination was not focused on erasing differences. Instead, we engaged with the idea that certain differences should matter less than they currently do in creating a safe and accessible public space for all.